PRONUNCIATION OF CONSONANTS /ð/ AND /θ/ BY ADULT VIETNAMESE EFL LEARNERS - Bui, Thien Sao (Universitas Pendidikan Indonesia, 2016)
This study examined the pronunciation of consonants /ð/ /θ/ by adult Vietnamese learners of English. Ten adult Vietnamese learners of English were selected to be the sample for the audiotape observation, which aimed at identifying the participants’ mistakes in pronouncing /ð/ and /θ/. Secondly, 115 learners of English in Vietnam were asked to complete a questionnaire regarding the causes of their pronunciation errors. The findings indicated that substitution phenomenon was a dominant problem in the students’ pronunciation of /θ/ and /ð/. The most outstanding problem in pronouncing the consonant /θ/ was replacing this sound by Vietnamese /t‘/. With regards to /ð/ sound, it was most frequently mispronounced as /z/. Besides, there was a new kind of mistake found: it was the tendency to pronounce /dʒ/ instead of /ð/, which has not been reported ever. Apart from that, participants also confirmed some causes of their erroneous pronunciation. As perceived by the learners themselves, the most popular causes of their problems were the lack of English exposure and practice, which implicated that an effective environment for using English was highly necessary.